Globalization and poverty: Evidence from a panel of countries in different income groups - Alper, Berk (My University, 2019)
Globalization refers to the phenomenon of increased capital and labor mobility and integration of related policies across the globe. Therefore, during the process of globalization, unprecedented developments, such as a much higher international trade level and the increased power of financial capital have played a central role in political, economic, and social developments. Despite observing its outcomes for almost half a century, the effects of globalization are still highly debated. The literature on this subject is rich with, often contradictory, results. On one hand, some authors claim that globalization decreases poverty, for example, through increasing growth rate. On the other hand, others claim that free trade and financial globalization exacerbate extreme poverty issue. In this paper, we examine the relationship between poverty and globalization for the countries from different income groups and levels of development and covering the period between 1990-2016. The results of our analysis, in which we used fixed effects panel data models, vary depending on the income level of countries. The evidence from the models denote that economic globalization is significantly and positively associated with poverty for middle and high income countries. Coefficients of trade globalization are found negative and significant for low and high income countries, which denotes that trade globalization decreases poverty in such countries; whereas the coefficient of financial globalization is found positive, and significant for only middle income countries. For all countries, coefficients of economic and financial globalization are found to be significant and positive while the coefficient of trade globalization is found to be insignificant.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2019
Keywords: Globalization; Poverty; International trade; Financial openness; Küreselleşme; Yoksulluk; Uluslararası ticaret; Finansal açıklık